The cyclical dynamics of industries in West Germany: Testing the industry life cycle hypothesis - Thomas Brenner; Matthias Dorner (Philipps-University Marburg, Department of Geography, 2015)
We test the industry life cycle hypothesis for 205 industries in West Germany between 1976 and 2009. In particular we analyse whether population indicators follow a cyclical path. Using a novel non-linear regression approach to identify life cycles we find that the number of establishments, employees, entries and exits follow in most industries a path that is well represented by at least a part of a cycle. Most industries that show cyclical behaviour run (partially) through their life cycle in the considered time period.
Keywords: C23; L16; O33; 330; industry life cycle; cyclical development; establishment; employment; industry dynamics